2020
DOI: 10.1016/j.apacoust.2019.07.019
|View full text |Cite
|
Sign up to set email alerts
|

Real-time active noise control with preservation of desired sound

Abstract: In the active sound control problem a quite arbitrary bounded domain is shielded from noise generated outside by implementing secondary sound sources on the perimeter. The sound generated by interior sources, also known as desired sound, is supposed to be protected inside the shielded domain. If the desired sound is present, it is required to remain it unaffected by the control. This problem becomes much more complicated since the secondary sources have a reverse effect on the input data. In the current paper,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 26 publications
(28 reference statements)
0
12
0
Order By: Relevance
“…The algorithm JASA is potentially applicable to realization in real-time regimes. It was implemented for the first time in the frequency domain by Zhou and Utyuzhnikov in (Zhou and Utyuzhnikov, 2020).…”
Section: Jasamentioning
confidence: 99%
See 2 more Smart Citations
“…The algorithm JASA is potentially applicable to realization in real-time regimes. It was implemented for the first time in the frequency domain by Zhou and Utyuzhnikov in (Zhou and Utyuzhnikov, 2020).…”
Section: Jasamentioning
confidence: 99%
“…This happens because the level of noise attenuation depends on the frequency. It is clear that the higher frequency the lower level of noise attenuation occurs (Epain and Friot, 2007;Zhou and Utyuzhnikov, 2020).…”
Section: B Mixed Sound Casementioning
confidence: 99%
See 1 more Smart Citation
“…A practical algorithm for real-time implementation of NASC is proposed in [42]. Zhou and Utyuzhnikov have recently realized this algorithm in both frequency and time domains in [44,45], respectively, and carried out numerical experiments including sensitivity analysis. In particular, it is shown that in the case of sparse distributions of the sensors and controls, the nonlocal control can provide much greater noise attenuation than the local control even if the primary field is supposed to be available.…”
Section: Introductionmentioning
confidence: 99%
“…More precisely, this effect occurs if the desired sound component is present and essential enough. As noted in [44], with a sparse distribution of sensors and controls the projection property of the potentials can be corrupted.…”
Section: Introductionmentioning
confidence: 99%